Health care factor and adherence of multimicronutrients consumption in mothers with children from 6 to 36 who come to the health center Guadalupe, Juliaca –2018 - Mamani Tito, Mayumy (2019)
Objective: the relationship between the health care factor and the adherence to multimicronutrientsconsumption in mothers with children from 6 to 36 months, Guadalupe Health Center, Juliaca - 2018.Metodology: It is a Correlational descriptive type study, quantitative approach, non-experimental andcross-sectional design. The sample was non-probabilistic of intentional type, using the inclusion andexclusion criteria, consisting of 70 children from 6 to 36 months of age. Instrument used for datacollection was the Lazarte multi-micronutrient health care factor test and adherence to consumption(2017). The results: Found indicate in relation to health care 60% perceived poor attention, 24.35perceived good care and only 15.7% perceived regular attention. Regarding adherence, 72.9% are notadherent and 27.1% were adherent to the consumption of multimicronutrients. Conclusion: there is adirect relationship between the health care factor and the adherence to multimicronutrient consumption,with a p-value of 0.000. Conclusion there is a significant relationship between both variables.